PENGARUH SOFT SKILL, MANAJEMEN TALENTA, DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PALOPO - Nur Azizah Sabir; Muhammad Kasran; Suparni Sampetan (Universitas Bina Taruna Gorontalo, 2023)
The purpose of this study was to analyze the influence of soft skills, talent management and transformational leadership on employee performance. The sample was taken by accidental sampling with 121 respondents.date were analyzed using a quantitative appoarch throught multiple regression analysis using the SPSS application. Soft skills are skills and life skills, both for yourselft, in grups or in society, as well as with are creator. In addition to soft skills, talent management is also key having strategic and sharp thinking, the ability to attract and inspire people, have entereneuprial instincts functionall skills and the ability to create result. The company also needs transformational leadership. This leadership is described as a leadership style that can arouse or mootivate employess. The result of the research coundcted show the soft skills, talent management, and transformational leadership have a positive and significant effect on employee performance simultanesously or partiallyTransformational Leadership